Tumour spillage of the pleomorphic adenoma of the parotid gland: A proposal for intraoperative measures - Mantsopoulos, Konstantinos; Iro, Heinrich (Oral Oncology, 2021)
Intraoperative rupture of a pleomorphic adenoma capsule with potential tumor spillage into the surgical field is thought to occur in approximately 5% of cases and has traditionally been recognized as one of the major causes of recurrence. It seems that recurrence of a pleomorphic adenoma is a multifactorial event, being related to surgery (capsular exposure, tumor spillage) and tumor-related factors (histologic subtype, incomplete capsule, pseudopodia, satellites). The exact quantities of these ingredients in the recipe of recurrence, as well as possible interactions between them (e.g. the potentially increased fragility of myxoid pleomorphic adenomas; satellites or pseudopodia being cut off the tumor specimen during an extremely narrow extracapsular dissection) remain unclear. A thorough literature search did not reveal any proposed algorithms for the intraoperative management of a capsular tear. The aim of this short communication is to present our department's experience-based proposal for intraoperative measures in the case of macroscopic rupture and tumor spillage of a parotid gland pleomorphic adenoma.
CRIS-Team Scopus Importer:2021-01-08